You are on page 1of 11

# Solutions Manual

to accompany

Communication
Systems
An Introduction to Signals and Noise in
Electrical Communication
Fourth Edition

A. Bruce Carlson
Rensselaer Polytechnic Institute

Paul B. Crilly
University of Tennessee

Janet C. Rutledge
University of Maryland at Baltimore
Solutions Manual to accompany
COMMUNICATION SYSTEMS: AN INTRODUCTION TO SIGNALS AND NOISE IN ELECTRICAL COMMUNICATION,
FOURTH EDITION
A. BRUCE CARLSON, PAUL B. CRILLY, AND JANET C. RUTLEDGE

Published by McGraw-Hill Higher Education, an imprint of The McGraw-Hill Companies, Inc., 1221 Avenue of the Americas,

The contents, or parts thereof, may be reproduced in print form solely for classroom use with COMMUNICATION SYSTEMS: AN
INTRODUCTION TO SIGNALS AND NOISE IN ELECTRICAL COMMUNICATION, provided such reproductions bear copyright
notice, but may not be reproduced in any other form or for any other purpose without the prior written consent of The McGraw-Hill
Companies, Inc., including, but not limited to, in any network or other electronic storage or transmission, or broadcast for distance
learning.

www.mhhe.com
Chapter 2

2.1-1
Ae jφ  Ae jφ n = m
∫− T0 / 2
T0 / 2
j 2 π ( m−n )f 0t jφ
cn = e dt = Ae sinc( m − n ) = 
T0 0 otherwise

2.1-2

c0 v (t ) = 0
2 T0 / 4 2π nt T0 / 2 2π nt 2A πn
cn =
T0 ∫
0
A cos
T0
dt + ∫ ( − A)cos
T0 / 4 T0
dt =
πn
sin
2

n 0 1 2 3 4 5 6 7
cn 0 2A/π 0 2 A / 3π 0 2 A / 5π 0 2 A / 7π
arg cn 0 ±180° 0 ±180°

2.1-3

c0 = v (t ) = A / 2
2 T0 /2  2 At  2π nt A A
cn =
T0 ∫ 0
A−
 T0 
 cos
T0
dt =
πn
sin π n −
(π n) 2
(cos π n − 1)

n 0 1 2 3 4 5 6
cn 0.5A 0.2A 0 0.02A 0 0.01A 0
arg cn 0 0 0 0

2.1-4

2 T0 / 2 2π t
c0 =
T0 ∫
0
A cos
T0
=0 (cont.)

2-1
2 A  sin (π − π n ) 2t / T0 sin (π + π n ) 2t / T0 
T0 / 2
2 T0 / 2 2π t 2π nt
cn =
T0 ∫0
A cos
T0
cos
T0
dt = 
T0  4(π − π n) / T0
+
4(π + π n ) / T0  0

A/2 n = ±1
[ sinc(1 − n) + sinc(1 + n )] = 
A
=
2  0 otherwise

2.1-5

c0 = v (t ) = 0
2 T0 / 2 2π nt A
cn = − j
T0 ∫0
A sin
T0
dt = − j
πn
(1 − cos π n )

n 1 2 3 4 5
cn 2A/π 0 2 A / 3π 2 A / 5π
arg cn −90° −90° −90°

2.1-6

c0 = v(t ) = 0
2 A  sin (π − π n ) 2t / T0 sin ( π + π n ) 2t / T0 
T0 / 2
2 T0 / 2 2π t 2π nt
cn = − j
T0 ∫0
A sin
T0
sin
T0
dt = − j 
T0  4(π − π n ) / T0

4(π + π n )/ T0  0

m jA / 2 n = ±1
[sinc(1 − n ) − sinc(1 + n ) ] = 
A
= −j
2  0 otherwise

2.1-7
1  T0 / 2
v ( t) e− jnω0 t dt + ∫ v(t )e − jnω 0t dt ]
T0
cn = ∫
T0  0 T0 / 2

T0 T0 / 2
where ∫T0 / 2
v(t )e − jnω0 t dt = ∫
0
v (λ + T0 /2) e− jnω 0λ e− jnω 0T0 / 2 d λ
T0 / 2
= −e jnπ ∫ v (t )e − jnω0 t dt
0

## since e jnπ = 1 for even n, cn = 0 for even n

2-2
2.1-8

P = c0 + 2 ∑ cn = Af 0τ + 2 Af 0τ sinc f 0τ + 2 Af 0τ sinc2 f 0τ + 2 Af 0τ sinc3 f 0τ + L
2 2 2 2 2 2

n =1

1
where = 4 f0
τ
1 1 + 2sinc2 1 + 2sinc2 1 + 2sinc2 3  = 0.23 A2
A2
f > P= 
τ 16 4 2 4 
2 A2  1 1 3 5 3 7
f > P= 1 + 2sinc2 + 2sinc2 + 2sinc2 + 2sinc2 + 2sinc 2 + 2sinc 2  = 0.24 A2
τ 16  4 2 4 4 2 4
1 A 
2
1 1
f > P= 1 + 2sinc2 + 2sinc 2  = 0.21A2
2τ 16  4 2

2.1-9
 0 n even

cn =  2 2
 π n  n odd
 
2 2
1 T0 / 2  4t  2 T0 / 2  4t  1
a) P =
T0 ∫−T0 / 2  1 − T0  dt = T0 ∫
0
 1 −  dt =
 T0  3
2 2 2
 4   4   4 
P′ = 2  2  + 2  2  + 2  2 
= 0.332 so P′ / P = 99.6%
π   9π   25π 
8 8 8
b) v′(t ) = 2 cos ω 0t + 2 cos3ω 0t + cos5ω 0t
π 9π 25π 2

2.1-10
 0 n even

cn =  − j 2
 π n n odd

1  2 2  2  2  2 2 
∫−T0 / 2 (1) dt = 1 P = 2  π  +  3π  +  5π   = 0.933 so P′ / P = 93.3%
T0 / 2
a) P = ′
2

T0  

(cont.)

2-3
4 4 4
b) v′(t ) = cos ( ω0t − 90° ) + cos ( 3ω0t − 90° ) + cos ( 5ω 0t − 90°)
π 3π 5π
4 4 4
= sin (ω 0t ) + sin ( 3ω 0t ) + sin ( 5ω0t )
π 3π 5π

2.1-11
2
1 T0  t  1 1 / 2 n=0
P=
T0 ∫0
  dt =
 T0  3
cn = 
1 / 2π n n ≠ 0
∞ 4 4
 2  2  1 1 1  1
P =2∑   = 2    4 + 4 + 4 +L =
n odd  π n  π  1 3 5  3

1 1 1 4π 2 1 1  π2
Thus, + + + L = 3− 4= 6
12 22 32 2  

2.1-12
2
2 T0 / 2  4t  1 0 n even
P=
T0 ∫0
 1 −  dt =
 T0  3
cn = 
 (2/ π n) n odd
2

∞2 2
1  1  1 2 1 1 1  1
P =   + 2∑   = + 2  2 + 2 + 2 +L =
2 n =1  2π n  4 4π 1 2 3  3

1 1 1 π4 1 π 4
Thus, 4 + 4 + 4 + L = =
1 3 5 2 ⋅ 24 3 96

2.2-1
πt
τ /2
V ( f ) = 2∫ cos2π ftdt
A cos
0 τ
τ
 π
(
 sin τ −2π f 2 sin ) ( πτ 2π f ) τ2  Aτ
+
= 2A  + = [ sinc( f τ −1/2) + sinc( f τ + 1/2) ]
 2 π −2π f
τ ( 2 ) (πτ 2π f )  2
+
 
(cont.)

2-4
2.2-2
τ /2 2π t
V ( f ) = − j 2∫ A sin cos2π ftdt
0 τ

 sin τ (
2π −2π f τ sin
) ( 2τπ 2π f ) τ2  = − j Aτ sinc( f τ −1) − sinc( f τ + 1)
+
= − j2 A  2− [ ]

(
 2 τ −2π f )2 ( 2τπ 2π f )  2
+

2.2-3
τ t 2 Aτ   ωτ  
V ( f ) = 2∫  A − A  cos ω tdt =  2sin 2   − 1 + 1 = Aτ sinc f τ
2

 τ (ωτ )   2 
2
0

2.2-4
τ t 2 Aτ
V ( f ) = − j 2∫ A sin ω tdt = − j (sin ωτ − ωτ cos ωτ )
0 τ (ωτ ) 2
A
= −j (sinc2 f τ − cos2π f τ )
πf

2.2-5
1  f 
v (t ) = sinc2Wt ↔ Π 
2W  2W 
2
∞ ∞ 1  f  ∞ 1 1
∫ sinc2Wt dt = ∫ df = ∫
2
Π  df =
−∞ −∞ 2W  2W  −∞ 4W 2
2W

2-5
2.2-6
2πW
( Ae − bt ) dt =
A2 A2 A2

E=∫ E′ = 2∫ 2
2W
df = arctan
0 2b 0 b + (2π f )2
πb b
E′ 2 2πW 50% W = b / 2π
= arctan =
E π b 84% W = 2b / π

2.2-7
∞ ∞
 ∞ W ( f ) e jω t df dt
∫−∞
v ( t )w ( t ) dt = ∫−∞
v( t )
 ∫−∞ 
∞ ∞ ∞
= ∫ W ( f )  ∫ v (t) e− j (− ω ) t dt  df = ∫ W ( f )V (− f ) df
−∞  −∞  −∞
∞ ∞ ∞
∫ v 2 ( t ) dt =∫ V ( f )V * ( f )df = ∫ V ( f ) df
2
V ( − f ) = V * ( f ) when v (t) is real, so
−∞ −∞ −∞

2.2-8
∗ ∗

∫−∞ w∗ (t)e− j 2π ft dt =  ∫−∞ w(t )e j 2π ft dt  =  ∫−∞ w( t)e− j 2π ( − f )t dt  = W ∗ ( f )
∞ ∞ ∞

Let z ( t ) = w∗ ( t ) so Z ( f ) = W ∗ ( − f ) and W ∗ ( f ) = Z ( − f )
∞ ∞
Hence ∫−∞
v( t )z( t) dt = ∫ V ( f ) Z ( − f ) df
−∞

2.2-9
t  1  f 
Π   ↔ A sinc Af so sinc At ↔ Π  
 A A  A
2t τ  fτ  2
v (t ) = sinc ↔ V ( f ) = Π   for A =
τ 2  2  τ

2.2-10
πt  t  Bτ
B cos Π   ↔ [ sinc( f τ − 1/2) + sinc( f τ + 1/2) ]
τ τ  2
Bτ π (− f )  − f  πf  f 
so [sinc(tτ − 1/2) + sinc(tτ + 1/2) ] ↔ B cos Π  = B cos Π 
2 τ  τ  τ τ 
Let B = A and τ = 2W ⇒ z (t ) = AW [sinc(2Wt − 1/2) + sinc(2Wt + 1/2) ]

2.2-11
2π t  t  Bτ
B sin Π  ↔− j [sinc( f τ − 1) + sinc( f τ + 1) ]
τ τ  2
Bτ 2π (− f )  − f  2π f  f 
so − j [ sinc(tτ − 1) + sinc( tτ + 1) ] ↔ B sin Π  = − B sin Π 
2 τ  τ  τ τ 
Let B = − jA and τ = 2W ⇒ z ( t ) = AW [ sinc(2Wt − 1) + sinc(2Wt + 1) ]

2-6
2.2-12
2b 4π a a /π
e −b t ↔ ⇒ e−2π a t ↔ = 2
b + (2π f )
2 2
(2π a ) + (2π f )
2 2
a + f2

(e )
2
∞ 2 1 ∞ a /π a ∞ df
∫ =∫ ∫
−2 π a t
dt = df = 2  
2π a −∞ a + f π  (a + f2)
−∞ 2 2 0 2
2

2
∞ dx 1 π  1 π
Thus, ∫ =   = 3
(a + x2 ) 2  a  2π a 4 a
0 2
2

2.3-1
z (t ) = v (t − T ) + v( t + T ) where v( t ) = AΠ (t /τ ) ↔ Aτ sinc f τ
so Z( f ) = V ( f ) e− jω T + V ( f )e jωT = 2 Aτ sinc f τ cos2π fT

2.3-2
z (t ) = v (t − 2T ) + 2v( t ) + v( t + 2T ) where v(t ) = aΠ (t /τ ) ↔ Aτ sinc f τ
Z ( f ) = V ( f )e − j 2ωT + V ( f ) + V ( f )e j2ωT = 2 Aτ (sinc f τ )(1 + cos4π fT )

2.3-3
z (t ) = v (t − 2T ) − 2v( t ) + v( t + 2T ) where v (t ) = aΠ (t /τ ) ↔ Aτ sinc f τ
Z ( f ) = V ( f )e − j 2ωT − 2V ( f ) + V ( f )e j2ωT = 2 Aτ (sinc f τ )(cos4π fT − 1)

2.3-4
 t −T   t −T / 2 
v (t ) = AΠ   + ( B − A)Π  
 2T   T 
− j ωT
V ( f ) = 2 AT sinc2 fTe + ( B − A)T sinc fTe− jω T / 2

2-7
2.3-5
 t − 2T   t − 2T 
v (t ) = AΠ   + ( B − A)Π  
 4T   2T 
V ( f ) = 4 AT sinc4 fTe − j 2ωT + 2( B − A)T sinc2 fTe− j 2ωT

2.3-6
1
Let w(t ) = v( at ) ↔ W ( f ) = V ( f / a)
a
1
Then z (t ) = v[a(t − td / a)] = w(t − td / a) so Z ( f ) = W ( f ) e− jω td / a = V ( f / a) e− jω td / a
a

2.3-7
∞ ∞
F  v (t) e jω ct  = ∫ v(t )e jω ct e− jω t dt =∫ v (t) e− j 2π ( f − fc ) t dt =V ( f − f c )
−∞ −∞

2.3-8
v (t ) = AΠ (t /τ )cos ωc t with ω c = 2π f c = π / τ
Aτ Aτ Aτ
V( f ) = sinc( f − f c )τ + sinc( f + f c )τ = [ sinc( fτ − 1/2) + sinc( f τ + 1/2) ]
2 2 2

2.3-9
v( t ) = AΠ (t /τ )cos(ωc t − π /2) with ω c = 2π f c = 2π / τ
e− jπ / 2 e jπ / 2
V( f ) = Aτ sinc( f − f c )τ + Aτ sinc( f + f c )τ
2 2

= −j [sinc( f τ − 1) − sinc( f τ + 1) ]
2

2.3-10
2A
z (t ) = v (t) c o s ω ct v(t ) = Ae − t ↔
1 + (2π f ) 2
1 1 A A
Z ( f ) = V ( f − fc ) + V ( f + fc ) = +
2 2 1 + 4π ( f − f c ) 1 + 4π ( f + f c )2
2 2 2

2.3-11
A
z (t ) = v ()cos(
t ωc t − π /2) v (t ) = Ae −t for t ≥ 0 ↔
1 + j 2π f
e − jπ / 2 e jπ / 2 − jA / 2 jA / 2
Z( f ) = V ( f − fc) + V ( f + fc ) = +
2 2 1 + j 2π ( f − f c ) 1 + j 2π ( f + f c )
A/2 A/2
= −
j − 2π ( f − f c ) j − 2π ( f + f c )

2-8
2.3-12
 A t
v (t ) = t z (t ) z (t ) = Π
 ↔ 2 A sinc2 f τ
 τ  τ
d d  sin2π f τ  2A
Z ( f ) = 2A   =  (2πτ )2 f cos2π f τ − 2πτ sin2π f τ 
2 
df df  2π f τ  (2π f τ )
1 d − jA
V( f ) = Z( f ) = ( sinc2 f τ − cos2π f τ )
− j 2π df πf

2.3-13
−b t 2 Ab
z (t ) = tv (t ) v( t ) = Ae ↔
b + (2π f )
2 2

1 d  2 Ab  j 2 Abf
Z( f ) =  2 2
=
− j 2π df  b + (2π f )   b + (2π f ) 2 
2
2
 

2.3-14
A
z (t ) = t 2v( t ) v (t ) = Ae −t for t ≥ 0 ↔
b + j2π f
1 d  A  2A
Z( f ) =  b + j 2π f  =
( − j 2π f )  [ b + j 2π f ]
2 3
df 

2.3-15
1
v (t ) = e−π (bt) ↔ V ( f ) = e −π ( f / b)
2 2

b
d j 2π f −π ( f / b)2
( a) v (t ) = −2π b 2te −π ( bt ) ↔
2
e
dt b
1 d f −π ( f / b )2
(b ) te− π (bt) ↔ V( f ) =
2
e
− j 2π df jb
Both results are equivalent to bte −π ( bt ) ↔ − jf e−π ( f / b)
2 2

2.4-1
y (t ) = 0 t<0
2
t At
= ∫ Aλ d λ = 0<t <2
0 2
2
= ∫0 Aλ d λ = 2A t >2